2012
DOI: 10.1073/pnas.1203525109
|View full text |Cite
|
Sign up to set email alerts
|

Secreted protein, acidic and rich in cysteine-like 1 (SPARCL1) is down regulated in aggressive prostate cancers and is prognostic for poor clinical outcome

Abstract: Prostate cancer is the second leading cause of cancer death among United States men. However, disease aggressiveness is varied, with low-grade disease often being indolent and high-grade cancer accounting for the greatest density of deaths. Outcomes are also disparate among men with high-grade prostate cancer, with upwards of 65% having disease recurrence even after primary treatment. Identification of men at risk for recurrence and elucidation of the molecular processes that drive their disease is paramount, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
73
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 50 publications
14
73
0
1
Order By: Relevance
“…The result indicates that SPARCL1 expression is negatively related to the malignant biological behavior of breast carcinogenesis. It is supposed that SPARCL1 may inhibit tumor growth and progression which has been confirmed by the findings with respect to SPARCL1 in prostate cancer (Hurley et al, 2012) and pancreatic cancer (Esposito et al, 2007).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The result indicates that SPARCL1 expression is negatively related to the malignant biological behavior of breast carcinogenesis. It is supposed that SPARCL1 may inhibit tumor growth and progression which has been confirmed by the findings with respect to SPARCL1 in prostate cancer (Hurley et al, 2012) and pancreatic cancer (Esposito et al, 2007).…”
Section: Discussionsupporting
confidence: 59%
“…In the growth and proliferation of various tumor cells, SPARCL1 often presents decreased expression as a negative regulative factor, which may be closely related to the increase of the cell proliferation activity and the cell cycle progression (Claeskens et al, 2000). Particularly, growing evidence shows that SPARCL1 often presents a reduced or absent expression pattern in a variety of human tumor tissues (Bendik et al, 1998;Nelson et al, 1998;Isler et al, 2004;Esposito et al, 2007;Zaravinos et al, 2011;Hurley et al, 2012;Li et al, 2012). However, several studies have also found that an increased expression of SPARCL1 in a few of other type of human tumors derived from liver (Lau et al, 2006), uterus (Mencalha et al, 2008), and colon and rectum (Zhang et al, 2011;Hu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPARCL1 is a member of the SPARC family of secreted matricellular proteins, together with SPARC/osteonectin, SMOCs, testicans, and follistatin-like protein 1 (37). SPARCL1 was shown to be a tumor suppressor in various cancers such as CRC (24), pancreatic cancer (54), and prostate cancer (55). SPARCL1 inhibits EC adhesion and spreading (38), but its direct impact on EC proliferation, migration, and capillary morphogenesis has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in CRC, the quiescence-inducing activity of SPARCL1 may contribute to the angiostatic micromilieu associated with a Th1-TME. In addition, SPARCL1 is secreted, and inhibitory effects on different tumor cell lines have been reported (24,54,55). Accordingly, SPARCL1 may be among the first EC-derived proteins with antitumorigenic activity, contributing to the positive prognosis associated with a Th1-TME.…”
Section: Transient Transfection Of Ecsmentioning
confidence: 99%